Our Australian girl - Wang, Gabrielle (Penguin Books / Puffin, 2014)
It's1942 and Pearlie is all alone in Darwin. Not only has she been separated from her family, but now Beake, the spy, is back and he's on the loose. He's out to get Pearlie - but she has a plan ... Can she pull it off? And when bombs fall on Darwin, will Pearlie survive? Follow Pearlie on her adventure in the third of four exciting stories about a courageous girl in a world at war